Animal and plant stem cells : concepts, propagation and engineering - Pavlovic, Mirjana (Springer, 2017)
This book provides a multifaceted look into the world of stem cells and explains the similarities and differences between plant and human stem cells. It explores the intersection between animals and plants and explains their cooperative role in bioengineering studies. The book treats both theoretical and practical aspects of stem cell research. It covers the advantages and limitations of many common applications related to stem cells: their sources, categories, engineering of these cells, reprogramming of their functions, and their role as novel cellular therapeutic approach. Written by experts in the field, the book focuses on aspects of stem cells ranging from expansion-propagation to metabolic reprogramming. It introduces the emergence of cancer stem cells and different modalities in targeted cancer stem cell therapies. It is a valuable source of fresh information for academics and researchers, examining molecular mechanisms of animal and plant stem cell regulation and their usage for therapeutic applications. Students at all levels of medical or engineering backgrounds will enjoy the case studies that illustrate and explain mechanisms, interactions, targeted effects, and multimodal therapeutic approaches. Academics, researchers, and professionals who want to expand their knowledge in this field will find this book an exceptional resource.
Keywords: Stem cells.; elektronické knihy; electronic books